8th Winter Shool of Quantum and Molecular Acoustics, and Sonochemistry, Ustroń–Jaszowlec 1979 - DOBRZAŃSKI, M. M. (Archives of Acoustics, 1979)
A successive Winter Shool of Quantum and Molecular Acoustics, and Sonochemistry took place in Ustroii-jaszowiec on March 5-10, 1979. It was organized under the interde¬partmental problem MR. I. 24 by the Higher Silesian Division of Polish Acoustical Society, Physics Institute of Silesian Technical University, Gliwice, and Institute of Fundamental Technological Research, Warsaw. The School was attended by 100 persons from 10 scientific centres.Compared to previous years, both the number of the attendees of the School and that of contributed papers were considerably greater. Therefore, in addition to plenary papers and reports on authors own investigations, round-table sessions and poster form presenta-tion of some papers, were introduced. Discussions took place in form of 6 sesions where 55 papers and communiqués deroted to the current state of investigations in the fields of quan¬tum and molecular acoustics, acoustoelectronics and acoustooptics, sonochemistry and ultrasonic spectroscopy were presented.